Taxonomy, palaeoecology and palaeobiogeography of some palaeozoic fish of Southern Gondwana - Evans, F. J. (Fiona Jocelyn) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2005.